2012
DOI: 10.1186/1735-2746-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4-chloro-2-nitrophenol adsorption on single-walled and multi-walled carbon nanotubes

Abstract: The adsorption characteristics of 4-chloro-2-nitrophenol (4C2NP) onto single-walled and multi-walled carbon nanotubes (SWCNTs and MWCNTs) from aqueous solution were investigated with respect to the changes in the contact time, pH of solution, carbon nanotubes dosage and initial 4C2NP concentration. Experimental results showed that the adsorption efficiency of 4C2NP by carbon nanotubes (both of SWCNTs and MWCNTs) increased with increasing the initial 4C2NP concentration. The maximum adsorption took place in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…The K ads estimation facilitated the modeling of the nature of P. muellerianus leaf-extract adsorption through use of the K ads for the separation factor, R L , computation in Equation (11) [56,60,65,66]:…”
Section: Adsorption Isotherm Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The K ads estimation facilitated the modeling of the nature of P. muellerianus leaf-extract adsorption through use of the K ads for the separation factor, R L , computation in Equation (11) [56,60,65,66]:…”
Section: Adsorption Isotherm Modelingmentioning
confidence: 99%
“…The R L computation, therefore, finds usefulness for indicating P. muellerianus leaf-extract adsorption on reinforcing-steel as irreversible if [60,66]. In addition to these, the K ads of the Langmuir isotherm model was used for estimating the Gibbs free energy of adsorption ∆G ads using Equation (12) [56,60,[62][63][64]:…”
Section: Adsorption Isotherm Modelingmentioning
confidence: 99%
“…The percentage removal of phenol increased with the increasing absorbent dosage (0.5-4.0 g). It is attributed due to increase in adsorbent surface area and availability of more adsorption sites (Mehrizad et al 2009;Uddin et al 2007). The results also revealed that the adsorption efficiency increases with the increasing dose (Rengaraj et al 2002).…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 99%
“…Among these methods, adsorption has been developed as a simple and cheap method to treat phenolic compounds. Various adsorbents such as bentonite [15], sawdust [16], activated carbon [17], nano-titanium dioxide [18], and carbon nanotubes [19] have been tested for adsorption of phenol and its compounds from aqueous solutions. Among them, carbon materials show significant adsorption yields.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, development of suitable methods for the decontamination of phenols is necessary. Research has studied the removal of phenol from aqueous solutions, including advanced oxidation processes [5,6], biological degradation [7,8], ozonation [9,10], adsorption [11][12][13][14] [19] have been tested for adsorption of phenol and its compounds from aqueous solutions. Among them, carbon materials show significant adsorption yields.…”
mentioning
confidence: 99%